Genus Rubia: Therapeutic Effects and Toxicity: A Review - Marzieh Eskandarzadeh; Akam Esmaeili; Mohammad Reza Nikbakht; Yukio Hitotsuyanagi; Yuri N Shkryl; Javad Ghasemian Yadegari; Hassan Rezazadeh; Javad Khalilifard * (Lorestan University of Medical Sciences, 2022)
The Rubiaceae family taxonomic classification is complex. Genus Rubia with 70 species belongs to Rubieae tribe of Rubioideae subfamily of the Rubiaceae family. These species have been widely distributed and cultivated around the world, and are mainly concentrated in the tropics. The effects of bioactive metabolites of various parts, particularly roots of Rubia species have been thoroughly examined, and their pharmacological and toxicological effects have been described. Antioxidant, anti-inflammatory, antitumor, antidiabetic, anti-arthritic, antiseizure and antimicrobial effects as well as toxicological properties of Rubia species have been previously reported. This study was conducted as a literature survey of various species of Rubiaceae published from 1992 to 2020. Moreover, their toxic and protective effects on living organisms were summarized.